Celiac disease and endocrine autoimmune disorders in children: an update. (December 2013) - Diamanti, Antonella; Capriati, Teresa; Bizzarri, Carla; Panetta, Fabio; Ferretti, Francesca; Ancinelli, Monica; Romano, Francesca; Locatelli, Mattia
Celiac disease (CD) is a life-long inflammatory condition of the gut that occurs in genetically susceptible individuals. Several autoimmune diseases (AI) are associated with CD. To date, no conclusive evidence is available that proves if the relationship between CD and AI is mediated by gluten exposure, or if CD and AI could co-occur due to other causes, in particular the loss of the intestinal barrier function and the common genetic background. Furthermore, it is not clear yet if CD needs a regular screening program for AI. This review will cover the key studies on both the pathogenetic and clinical evidence explaining this association. We will review the reports including patients aged <18 years with CD and endocrine AI.